Enhancing Campus Familiarity: A Comparative Study of Augmented and Mixed Reality Applications for UMSIDA Campus 2 - Cindy Taurusta; Nuril Lutvi Azizah; Ferry Adhi Dharma; Vini Rahmawati; Afnizar Maulana Asiddiq (Indonesian Journal of Cultural and Community Development, 2023)
This study addresses the need for improved orientation among Muhammadiyah University of Sidoarjo (UMSIDA) students, particularly newcomers unfamiliar with the layout of Campus 2. Leveraging the Multimedia Development Life Cycle (MDLC) Method, researchers developed and compared Augmented Reality (AR) and Mixed Reality (MR) applications, utilizing Faculty of Science and Technology brochures to render 3D representations of UMSIDA Campus 2 buildings. An online questionnaire garnered feedback from 25 UMSIDA students, with 88% expressing approval for the AR-based introduction application. To better assess its impact on prospective student enrollment, PMB Team members were consulted, resulting in 66.7% favoring the MR application for its enhanced engagement. Notably, both AR and MR applications were deemed equally useful by 66.7% of respondents. Consequently, these applications will be integrated into a comprehensive solution for further evaluation and optimization. This research underscores the potential of immersive technologies in enhancing campus navigation and highlights the significance of user preference in educational applications of augmented and mixed reality. Highlight: Utilizing MDLC Method: The study leverages the Multimedia Development Life Cycle (MDLC) Method for the development and comparison of Augmented Reality (AR) and Mixed Reality (MR) applications, targeting improved campus orientation for UMSIDA students. User Preference in Immersive Technologies: Feedback from UMSIDA students and PMB Team members revealed a preference for the Mixed Reality (MR) application, emphasizing the significance of user preference in educational applications of augmented and mixed reality. Integration for Enhanced Effectiveness: The AR and MR applications will be integrated into a comprehensive solution, highlighting the commitment to ongoing evaluation and optimization to further enhance campus navigation for UMSIDA students. Keyword: Orientation, Augmented Reality, Mixed Reality, Campus Navigation, Immersive Technologies